Repositioning of Religious Moderation in Indonesia: a Conceptual Analysis Review with Phenomenology Approach - Prayogo, Tonny Ilham; Zarkasyi, Amal Fathullah; Arroisi, Jarman; Indah, Nurmala (LPPM IAIN Kudus, 2024)
Religious diversity in Indonesia is confronted with two significant challenges. The first is the challenge posed by those who espouse radical or liberalist views, while the second is the refraction of religious pluralism by those who equate its main objectives. Consequently, the presence of religious moderation represents a viable approach to fostering tolerance and harmony between religious communities. The objective of this research is to examine the values of religious moderation in the context of al-Wasathiyyah al-Islamiyyah, with a view to identifying potential solutions. This type of research is a literature review (LR) that analyses and synthesises the strengthening of religious moderation according to al-Wasathiyyah al-Islamiyyah. Accordingly, to buttress this line of inquiry, the researcher has adopted a descriptive-analytical approach, complemented by a religious phenomenology methodology. The findings of this study indicate that al-Wasathiyyah al-Islamiyyah is characterised by a set of prioritised indicators, namely the maintenance of al-Maqashid asy-Syari’ah on religious freedom, unity on the purpose of life, unity on life guidelines, and unity on human diversity. In order to maintain the unity of multicultural Indonesian society, it is necessary to create an atmosphere of justice, peace, harmony and tolerance. This will enrich the inclusive and progressive Islamic discourse in the contemporary era.